Takotsubo Syndrome: Cardiotoxic Stress in the COVID Era - O’Keefe, Evan L. (Mayo Clin Proc Innov Qual Outcomes, 2020)
Takotsubo syndrome (TTS), also known as stress cardiomyopathy and broken heart syndrome, is a neurocardiac condition that is among the most dramatic manifestations of psychosomatic disorders. This paper is based on a systematic review of TTS and stress cardiomyopathy using a PubMed literature search. Typically, an episode of severe emotional or physical stress precipitates regions of left ventricular hypokinesis or akinesis, which are not aligned with a coronary artery distribution and are out of proportion to the modest troponin leak. A classic patient with TTS is described; one who had chest pain and dyspnea while watching an anxiety-provoking evening news program on the coronavirus disease 2019 (COVID-19) pandemic. An increase in the incidence of TTS appears to be a consequence of the COVID-19 pandemic, with the TTS incidence rising 4.5-fold during the COVID-19 pandemic even in individuals without severe acute respiratory syndrome coronavirus 2 infection. Takotsubo syndrome is often mistaken for acute coronary syndrome because they both typically present with chest pain, electrocardiographic changes suggesting myocardial injury/ischemia, and troponin elevations. Recent studies report that the prognosis for TTS is similar to that for acute myocardial infarction. This review is an update on the mechanisms underlying TTS, its diagnosis, and its optimal management.